Efikasi Ekstrak Daun dan Bunga Kecombrang (Etlingera elatior) terhadap Larva Aedes aegypti - Meiske Elisabeth Koraag; Hayani Anastasia; Rina Isnawati; Octaviani Octaviani (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Three widely known dengue vector control programs in Indonesia are chemical, biological, and environmental modification control where chemical control with organophosphate insecticide (malathion and temephos) is the most common. The long term use of chemical insecticide will result in the vector being tolerant and eventually resistant to insecticide. One of the alternative solutions is to use biological larvacide from the plant. The objective of this study was to determine the lethal concentration of the extract of Kecombrang (Etlingera elatior) leaves and flowers against Aedes aegypti larvae. This was an experimental study where the sample size was determined by using the Federer formula. The study used six different concentrations and four repetitions. Two controls group, Bacillus thuringiensis and water used as positive and negative control. The results showed that the LC50 and LC90 of Kecombrang leave extract were 1.20% and 2.05% respectively whereas for Kecombrang flowers extract were 0,05% and 0.09% respectively. Extract of Kecombrang leaves and flowers is effective to kill Ae. aegypti larvae where the flowers extract is more effective than the leaves extract in killing Ae. aegypti larvae.